1979
DOI: 10.1128/jb.139.2.701-704.1979
|View full text |Cite
|
Sign up to set email alerts
|

Conditional-lethal deoxyribonucleic acid ligase mutant of Escherichia coli

Abstract: A new Escherichia coli deoxyribonucleic acid (DNA) ligase mutant has been identified among a collection of temperature-sensitive DNA replication mutants isolated recently (Sevastopoulos, Wehr, and Glaser, Proc. Natl. Acad. Sci. U.S.A. 74:3485-3489, 1977). At the nonpermissive temperature DNA synthesis in the mutant stops rapidly, the DNA is degraded to acid-soluble material, and cell death ensues. This suggests that the mutant may be among the most ligasedeficient strains yet characterized.DNA ligase plays an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…Measurements of the rate of DNA synthesis in the ligA251 mutant switched to ligase-deficient conditions show that the rate is stable for at least 5 min at 42°C, but then drops to 30% by 15 min and to 20% by 45 min (Fig. 1E), which is consistent with the observations of others (Dermody et al, 1979). We conclude that LDD is due to a single round of ligase-deficient replication, which continues at near-normal rates for several minutes before being inhibited, the timing of inhibition preceding the timing of RED.…”
Section: Figsupporting
confidence: 91%
See 2 more Smart Citations
“…Measurements of the rate of DNA synthesis in the ligA251 mutant switched to ligase-deficient conditions show that the rate is stable for at least 5 min at 42°C, but then drops to 30% by 15 min and to 20% by 45 min (Fig. 1E), which is consistent with the observations of others (Dermody et al, 1979). We conclude that LDD is due to a single round of ligase-deficient replication, which continues at near-normal rates for several minutes before being inhibited, the timing of inhibition preceding the timing of RED.…”
Section: Figsupporting
confidence: 91%
“…To a lesser extent, this behaviour was also noticed in the ligA7 mutant, allowing the authors to postulate formation of double-strand breaks at the sites of unsealed single-strand gaps between Okazaki fragments (Pauling et al, 1976). In fact, the weaker ligA mutations, when combined with polA mutations inactivating DNA polymerase I, the other enzyme besides ligase that participates in maturation of Okazaki fragments, display a grossly perturbed chromosomal replication at the nonpermissive temperatures and a rapid loss of viability, associated with significant degradation of template DNA strands (Gottesman et al, 1973a;Horiuchi and Nagata, 1974;Konrad et al, 1974;Horiuchi et al, 1975), just like what we [and others (Dermody et al, 1979)] observed in ligA251 single mutants. In summary, all these effects of ligase-deficient replication could be economically ascribed to the inability to seal Okazaki fragments in the nascent DNA strands.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…E. coli GE1720 (provided by Dr. Sigr ıdur H. Thorbjarnard ottir, University of Iceland) was used as the host for in vivo complementation test of DNA ligase activity. This strain carries the ligts251 mutation which had previously been shown to cause loss of viability at 41°C due to inability to perform ligation of Okazaki fragments [10].…”
Section: Methodsmentioning
confidence: 99%
“…Genetic studies show that mutations that inactivate the activity of E. coli DNA ligase are lethal to the cell [5,6]. Temperature-sensitive point mutations in the E. coli ligA gene were isolated and E. coli strains carrying these conditional mutations failed to grow at non-permissive temperatures [6][7][8][9][10][11]. The viability of these E. coli strains was significantly reduced immediately after the cells were incubated at non-permissive temperatures [6][7][8]10].…”
mentioning
confidence: 99%